Comprehension and definition of compound words in children with autism spectrum disorder (ASD) - Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2018)
Background: More insight is needed into the mechanisms that underlie co-morbid language impairments in children with ASD across complex lexical and/or grammatical phenomena, particularly for languages beyond English. Aim/s: To test the comprehension and production of two-constituent compound words at the single-word level for Greek (e.g., pondikopayitha ‘mouse trap’) in four school-aged children (mean age 7; 8 years) diagnosed with ASD. Method: Comprehension was probed in relation to the word’s constituents, for which semantic interpretation involved explaining the meaning of the compound. This involved the examiner introducing the child to a puppet and asking the child to tell the puppet: “Why do we say X?” For carrot juice, one of the warm up examples used the experimenter asked: ‘We say carrot juice because it is juice from a carrot, right?’ Each response was coded at two levels, one that related to comprehension (i.e., parsing of the NNC) and one that tapped into semantic interpretation of the NNC (i.e., explaining). Production of compound words was tested using a picture confrontation naming task. Results: The results revealed that the children with ASD had less difficulty parsing the compound constituents but showed a significant deficit in deriving the compound meaning. Naming compounds was exceptionally difficult for the ASD group despite generally intact comprehension of the object pictures. Conclusion: It is hypothesized that children with ASD have difficulties at the interface of (morpho) syntax with semantics and pragmatics, that is, at the conceptual-intentional system.
Keywords: Autism spectrum disorder; Two-constituent compound